The Level of Knowledge, Attitude and Behavior of Medical Students Yarsi University Class of 2021 and 2022 Regarding The Use of Electric Cigarettes and Its Review From The Islamic Aspect - Altrimeifo Putra, Nabiel; Poerwanto, Eko; Arsyad, Muhammad (Junior Medical Journal, 2024)
ABSTRAK Latar Belakang: Rokok digambarkan sebagai produk tembakau yang dibungkus, seperti cerutu atau bentuk lain yang mencakup bahan berbahaya di dalamnya. Indonesia berada di posisi ketiga, setelah Cina dan India dalam hal konsumsi rokok. Terdapat tren baru di Indonesia yaitu penggunaan rokok elektrik. Bagi perokok yang saat ini memiliki kebiasaan merokok, rokok elektrik adalah alat yang digunakan untuk mengurangi kecanduan tembakau. Rokok elektrik sudah mendapatkan hak paten di semua negara, termasuk Indonesia. Metode: Digunakan metode penelitian kuantitatif observasional analitik dengan pendekatan cross sectional. Dengan teknik quota sampling diperoleh 325 sampel. Kemudian data dianalisis menggunakan uji hipotesis chi-square. Hasil: Terdapat 150 responden (46,2%) angkatan 2021 dan 175 responden (53,8%) angkatan 2022. Diperoleh 64,9% responden yang memiliki pengetahuan baik mengenai rokok elektrik didominasi oleh angkatan 2021, 60% responden yang memiliki sikap menolak rokok elektrik didominasi oleh angkatan 2022, dan 83,4% responden yang memiliki perilaku menolak rokok elektrik didominasi oleh angkatan 2022. Dari uji chi-square diperoleh p-value pengaruh tingkat pendidikan terhadap pengetahuan, sikap dan perilaku mengenai penggunaan rokok elektrik secara berturut-turut adalah 0,488; 0,088; dan 0,441. Simpulan: Tidak terdapat pengaruh tingkat pendidikan terhadap pengetahuan, sikap, dan perilaku mengenai penggunaan rokok elektrik pada mahasiswa Fakultas Kedokteran Universitas YARSI angkatan 2021 dan 2022. ABSTRACT Background: Cigarettes are described as wrapped tobacco products, such as cigars or other forms that include dangerous ingredients inside. Indonesia is in third position, after China and India, in terms of cigarette consumption. There is a new trend in Indonesia, namely the use of electronic cigarettes. For smokers who currently have a smoking habit, e-cigarettes are a tool used to reduce tobacco addiction. E-cigarettes have received patent rights in all countries, including Indonesia. Method: Quantitative analytical observational research methods were used with a cross sectional approach. With the quota sampling technique, 325 samples were obtained. Then the data was analyzed using the chi-square hypothesis test. Result: There were 150 respondents (46.2%) class of 2021 and 175 respondents (53.8%) class of 2022. It was found that 64.9% of respondents who had good knowledge about e-cigarettes were dominated by the class of 2021, 60% of respondents who had an attitude of rejecting e-cigarettes dominated by the class of 2022, and 83.4% of respondents who had the behavior of rejecting e-cigarettes were dominated by the class of 2022. From the chi-square test, it was obtained that the p-value of the influence of education level on knowledge, attitudes, and behavior regarding the use of e-cigarettes respectively was 0.488; 0.088; and 0.441. Conclusion: There is no influence of education level on knowledge, attitudes and behavior regarding the use of e-cigarettes among medical faculty students YARSI University class of 2021 and 2022